Dinâmica de transmissão natural de Mansonella ozzardi (Manson, 1897) (Nematoda: Onchocercidae) na comunidade de Pedras Negras, município de São Francisco do Guaporé, Estado de Rondônia, Brasil - Velasques, Suzane Neves (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
Mansonelliasis is a tropical filarial disease caused by M. ozzardi transmitted by black flies and midges. Only the black flies are vectors for this filariasis in Brazil, where the disease is more expressive in Amazonian riverside communities. This gives to Rondônia State a real risk of occurrence of this filariasis. This study investigated the natural occurrence of M. ozzardi in anthropophilic blackflies species collected and the epidemiological risk factors for mansonelliasis at the Remaining Community of Quilombo Pedras Negras, in the Guapore Valley, Rondônia State. Collections of four days per month between November 2011 and October 2012 were held from 6:00 to 18:30, with 30 minutes interval during which we analyzed the parity of females captured. A two species were collected biting: Cerqueirellum pydanieli and Coscaroniellum quadrifidum. There was a higher abundance of parous females. The M. ozzardi larvae were found in all stages of development. A larger sample of black flies occurred during the rainy season, which were restricted collections of C. quadrifidum. The biting activity was higher in the afternoon for both species of black flies. The climatic parameters temperature and humidity were considered influential in the C. pydanieli activity. There were no significant correlations with the other variables, nor between these and C. quadrifidum. The parasitic infection rates were considered low and the potential annual transmission was considered high compared to other studies. Until now, no case records of mansonelliasis in Rondônia, however, both C. pydanieli as C. quadrifidum were positive for infection by M. ozzardi with specimens containing metacyclic larvae, indicating that both species are probable carries of this filaria in the Guapore Valley, Rondônia State, Brazil.
Keywords: Mansonella ozzardi; Parasitas; Manson